Keabsahan Tindakan Pemerintah Dalam Pemberhentian Dan Pengangkatan Pengganti Anatarawaktu Anggota Saniri Negeri - Galeb, Yunasril La; Nendissa, Renny Heronia; Saija, Vica Jillyan Edsti (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: In carrying out or issuing decisions or actions, the government must determine based on authority, in Article 8 paragraph (2) of Law Number 30 of 2014 concerning Government Administration states that: